Contemporary issues in Islam - Afsaruddin, Asma, 1958- (Edinburgh : Edinburgh University Press, 2015)
This book deals with certain ""hot-button"" contemporary issues in Islam that are often the focus of public scrutiny, including the Sharia, jihad, the caliphate, women's status, and interfaith relations. Notably, it places the discussion of these topics within a longer historical framework in order to reveal their multiple interpretations and contested applications over time. Most public and some academic discourses however present the Islamic tradition as unchanging and therefore unable to respond to the modern world. Such an ahistorical approach fosters the belief that Muslim and Western soc.
Includes bibliographical references and index.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Islam -- History -- 21st century; Islam and politics; Islamic law; Women in Islam; Muslims -- United States; Religion -- Islam -- History; Islam; Islam and politics; Islamic law; Muslims; Women in Islam; United States; RELIGION / Islam / General; 2000-2099; Electronic books; History